An evaluation of the coach segment of a story-based positive youth development program for youth ice hockey athletes - Maw, A.; Profeit, M. C.; Benson, A. J.; Mcguire, C. S.; Saizew, K.; Murata, A.; Erickson, K.; Côté, J.; Wolff, M.; Ladd, B.; Martin, L. J. (International Sport Coaching Journal, 2026)
Coaches help shape sport environments and athlete experiences. However, many coach development programs do not adequately teach the knowledge and skills necessary for holistic athlete development. Accordingly, a positive youth development program, the 1616 Program (1616), was created to foster developmentally rich opportunities for youth ice hockey players. To overcome many current coach development program shortcomings, 1616 includes a coach-specific segment grounded in coaching effectiveness, leadership, and behavior change literature. We explored the coach segment`s impact using a mixed-method convergent parallel design with coaches across North America. In total, 36 coaches ( n = 3 females; M age = 43.8 years; SD = 5.33 years) with an average of 10.1 years ( SD = 8.04) of coaching experience completed questionnaires. We interviewed nine coaches ( n = 1 female; M age = 43.0 years; SD = 8.04 years) with an average of 8.5 years ( SD = 3.73) of coaching experience. Results suggest that coaches felt that athlete personal assets improved while describing improvements in their own behavior change markers, efficacy beliefs, and interpersonal and leadership skills. Despite noting areas for improvement, coaches who completed the 1616 Program generally improved their self-perception, experienced more positive athlete interactions, and appreciated the high-quality program design and delivery.